Spontaneous Regression of Choroidal Neovascularization in a Patient with Pattern Dystrophy. (26th October 2016) - Anastasakis, Anastasios; Goleni, Flamur; Livir-Rallatos, Gerasimos; Livir-Rallatos, Charalampos; Zafirakis, Panagiotis; Allen Fishman, Gerald
Abstract : Purpose . To present a case of a patient with pattern dystrophy (PD) associated choroidal neovascularization (CNV) that resolved spontaneously without treatment. Methods . A 69-year-old male patient was referred to our unit, for evaluation of a recent visual loss (metamorphopsias) in his left eye. Fundus examination, fundus autofluorescence imaging, and fluorescein angiography showed a choroidal neovascular membrane in his left eye. Since visual acuity was satisfactory the patient elected observation. Clinical examination and OCT testing were repeated at 6 and 12 months after presentation. Results . Visual acuity remained stable at the level of 0.9 (baseline BCVA) during the follow-up period (12 months). Repeat OCT testing showed complete spontaneous regression of the choroidal neovascular membrane without evidence of intra- or subretinal fluid in both follow-up visits. Conclusions . Spontaneous regression of choroidal neovascularization can occur in patients with retinal dystrophies and associated choroidal neovascular membranes. The decision to treat or observe these patients relies strongly on the presenting visual acuity, since, in isolated instances, spontaneous resolution of choroidal neovascularization may occur.